The Influence of Benefits, Convenience and Risks on Interest in Using Mobile Banking Through a Positive Attitude as an Intervening Variable - Sitio, Ricky; Nurjanah, Siti (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
COVID-19 has changed the way things are done. To reduce the financial spread of the COVID-19, people choose to make non-cash financial transactions during the COVID-19. This study aims to determine and analyze the magnitude of the influence of benefits, convenience and risks on interest in using m-banking through a positive attitude at Bank Ina Perdana KCP Kelapa Gading. The research population consisted of 506 customers of Bank Ina KCP Kelapa Gading, total sample of 223 people. The results of the study are benefits, convenience and risks have a significant positive effect on positive attitudes in using Bank Ina's m-banking, benefits, convenience, risks and positive attitudes have a significant positive effect on interest in using Bank Ina's m-banking, positive attitudes can mediate in full variable benefits and risk variables on interest in using Bank Ina's m-banking, while a positive attitude cannot mediate ease of interest in using Bank Ina's m-banking.